The 23rd IEEE International Symposium on Robot and Human Interactive Communication 2014
DOI: 10.1109/roman.2014.6926274
|View full text |Cite
|
Sign up to set email alerts
|

Experience of using a haptic interface to follow a robot without visual feedback

Abstract: Abstract-Search and rescue operations are often undertaken in smoke filled and noisy environments in which rescue teams must rely on haptic feedback for navigation and safe exit. In this paper, we discuss designing and evaluating a haptic interface to enable a human being to follow a robot through an environment with no-visibility. We first discuss the considerations that have led to our current interface design. The second part of the paper describes our testing procedure and the results of our first tests. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The handle is attached to the robot with a flexible joint (spring system) and aligned with the center line of the robot, refer to Fig.1 left. The handle can rotate in the horizontal plane, and rotation induces tension on the handle; this induces the best robot following behaviour as [3] has shown.…”
Section: Robot and Interfacementioning
confidence: 93%
See 4 more Smart Citations
“…The handle is attached to the robot with a flexible joint (spring system) and aligned with the center line of the robot, refer to Fig.1 left. The handle can rotate in the horizontal plane, and rotation induces tension on the handle; this induces the best robot following behaviour as [3] has shown.…”
Section: Robot and Interfacementioning
confidence: 93%
“…In addition also combined activations can be thought of. However, [3] found that subjects tend to perceive this as a single, more intense, signal. When a handler is navigating an environment, certainly when unknown, new data/information about the area in front is the most relevant.…”
Section: B Feedback Provisionmentioning
confidence: 93%
See 3 more Smart Citations